Neuron-specific prolyl-4-hydroxylase domain 2 knockout reduces brain injury after transient cerebral ischemia - Kunze, Reiner; Zhou, Wei; Veltkamp, Roland; Marti, Hugo (Stroke, 2012)
Background and Purpose: Numerous factors involved in the adaptive response to hypoxia, including erythropoietin and vascular endothelial growth factor are transcriptionally regulated by hypoxia-inducible factors (HIFs). During normoxia, prolyl-4-hydroxylase domain (PHD) proteins hydroxylate HIF-α subunits, resulting in their degradation. We investigated the effect of neuronal deletion of PHD2, the most abundant isoform in brain, for stroke outcome.Methods: We generated neuron-specific Phd2 knockout mice and subjected animals to systemic hypoxia or transient middle cerebral artery occlusion. Infarct volume and cell death were determined by histology. HIF-1α, HIF-2α, and HIF target genes were analyzed by immunoblotting and real-time polymerase chain reaction, respectively. Results: Neuron-specific ablation of Phd2 significantly increased protein stability of HIF-1α and HIF-2α in the forebrain and enhanced expression of the neuroprotective HIF target genes erythropoietin and vascular endothelial growth factor as well as glucose transporter and glycolysis-related enzymes under hypoxic and ischemic conditions. Mice with Phd2-deficient neurons subjected to transient cerebral ischemia exhibited a strong reduction in infarct size, and cell death of hippocampal CA1 neurons located in the peri-infarct region was dramatically reduced in these mice. Vessel density in forebrain subregions, except for caudate-putamen, was not altered in Phd2-deficient animals. Conclusions: Our findings denote that the endogenous adaptive response on hypoxic-ischemic insults in the brain is at least partly dependent on the activity of HIFs and identify PHD2 as the key regulator for the protective hypoxia response. The results suggest that specific inhibition of PHD2 may provide a useful therapeutic strategy to protect brain tissue from ischemic injury.